Exploring Self - Confidence Level of High School Students Doing Sport - Nurullah Emir Ekinci; Çetin Özdilek; Gamze Deryahanoğlu; Ümit Doğan Üstün (ümit doğan üstün, 2014)
The aim of this study was to investigate self-confidence levels of high school students, who do sport, in the extent of their gender, sport branch (individual/team sports) and aim for participating in sport (professional/amateur). 185 active high school students from Kutahya voluntarily participated for the study. In the study as data gathering tool self-confidence scale was used. In the evaluation of the data as a hypothesis test Mann Whitney U non parametric test was used. As a result self-confidence levels of participants showed significant differences according to their gender and sport branch but there was no significant difference according to aim for participating in sport.